Legal Consciousness in the Digital Era: Challenges of Disinformation and Cybercrime - Johanes De Brito Siga Nono; Stefanus Kurniadi Janggur; Rizal Simon Thene (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This article examines the transformation of legal consciousness in the digital era and analyzes how disinformation and cybercrime contribute to its degradation, while also exploring the implications of these phenomena for legal compliance, regulatory adaptation, and the development of more responsive and preventive legal frameworks in contemporary digital society. Research Methodology: Employing a normative legal research method with conceptual approaches, this study reconstructs legal consciousness beyond mere knowledge of rules or formal compliance, redefining it as a reflective capacity to recognize legal risks, critically filter information, and act responsibly in digital spaces. Results: The normative-analytical findings reveal that reactive and repressive regulatory responses tend to neglect the dimension of legal consciousness, potentially undermining legal legitimacy and generating tension with digital freedom. This indicates that law enforcement approaches that rely solely on sanctions may not fully address behavioral compliance in digital environments. Conclusions: This study asserts that digital transformation has fundamentally altered the manner in which law operates and is complied with in contemporary society, requiring more adaptive and participatory legal mechanisms. Limitations: As this research is primarily conceptual, it does not include empirical measurements or quantitative assessments of the effectiveness of existing legal policies, which limits generalizability. Contributions: The article proposes a preventive-oriented framework of digital legal consciousness as a foundation for more adaptive legal policies aimed at sustaining legal order within an increasingly complex digital society, while strengthening compliance through awareness-based regulation.